Innovation of extract (Lawsonia Inermis L) as alternative dye for Escherichia Coli bacterial staining - Niken, Niken; Yulia, Inelvi (PT. Riset Press International, 2023)
Escherichia coli (E.coli) is a group of gram-negative bacteria that are part of the normal flora in the body. Under certain conditions, these bacteria can be pathogenic by producing enterotoxins that can cause serious infections such as diarrhea. Establishing the diagnosis of infection due to E.coli bacteria, namely through laboratory tests by identifying the bacteria through the bacterial staining method. So far, the most widely used bacterial dyes are synthetic dyes such as safranin. Safranin is a dye in Gram stain which can be carcinogenic and in the long run has a negative impact on health. To overcome this problem, it is necessary to innovate natural dyes that can be used as alternative dyes. Leaves of henna nails (Lawsonia inermis L.) is one of the natural ingredients which has an orange-orange lawsone pigment that is able to color the cell walls of gram-negative bacteria such as E.coli. The purpose of this study was to determine the ability of henna leaf extract (Lawsonia inermis L.) as an alternative to safranin staining. This research is a laboratory experiment. The experimental group was stained with henna leaf extract, using ethanol solvent concentrations of 25 mg/ml, 50 mg/ml, 75 mg/ml and 100 mg/ml. The control group used safranin dye. All research groups were carried out 3 repetitions. The parameters used were the clarity of the visual field, the shape of the bacteria, the cleanliness of the preparation and the color of the bacteria compared to the safranin control. The results showed that henna leaf extract was effective enough to be used as a coloring agent to replace safranin because it can color E.coli bacteria well.